Radiological Patterns of Bronchogenic Carcinoma in a Sample of Iraqi Patients - Dawood, Haider N.; Sameen, Mohammed I.; Al-Khairalla, Mudher (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Bronchogenic carcinoma is considered one of the most common malignant diseases that affects both sexes. The radiological profile of bronchogenic cancer can prove to be of great assistance in the management of this disease.Objectives: The current study aimed to assess a radiological profile for bronchogenic carcinoma in a sample of Iraqi patients.Methods: A cross-sectional study that comprised a total of 100 patients affected with bronchogenic cancer in Al-Imamain Al-Kadhimain Medical City, Baghdad, Iraq, from the 1st of January to 31st  of July 2020. Clinical characteristics, diagnostic modalities, the site of the tumor within the lung, radiological findings, and the histopathologic type of cancer, were recorded.  Results: The subjects consisted of 100 patients affected with bronchogenic carcinoma, 70% were males and 30% were females, and the mean age was 62.26±10.8 years. Also, 59% were ex\current smokers. The site of the tumour, according to the CT scan, was 44% in the left lung, 40% in the right lung, and 16% bilaterally. The most common histopathological type was squamous cell carcinoma, accounting for 44% of patients; the second type was adenocarcinoma (39%). The radiological findings showed 53% of the cases, the cancer was seen as a mass on imaging, while in 35% a solitary nodule was foundConclusions:  Lung mass and lung nodules are the most common radiological findings in bronchogenic carcinoma. There was no significant association between the radiological finding, site of lesion, and histopathological type.